1968
DOI: 10.1159/000129967
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of karyotypes in the Camelidae

Abstract: The Old World camels of the genus Camelus have diverged from the New World camels of the genera Lama and Vicugna over a period of more than a million years of their evolution. The two groups of modern camelids have evolved numerous different adaptations, but they retain a number of phenotypic similarities. Chromosome preparations made in this laboratory from cultured cells of various tissues demonstrate notable similarity of the karyotypes of two Old World camelids and one of the New World forms. Comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

1969
1969
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 0 publications
2
22
0
2
Order By: Relevance
“…The synteny between the Bactrian camel and cattle genomes observed in the present study is greater than that reported previously 3 . Our study supports the notion that divergent evolution in Camelidae occurred through single gene mutations or minor chromosomal rearrangements 5 . We estimated the segmental duplication of these three individuals: the total length of segmental duplication in both the Bactrian camel and dromedary was 26 Mb, smaller than that of the alpaca (36 Mb) (Supplementary Table 15).…”
Section: Resultssupporting
confidence: 89%
“…The synteny between the Bactrian camel and cattle genomes observed in the present study is greater than that reported previously 3 . Our study supports the notion that divergent evolution in Camelidae occurred through single gene mutations or minor chromosomal rearrangements 5 . We estimated the segmental duplication of these three individuals: the total length of segmental duplication in both the Bactrian camel and dromedary was 26 Mb, smaller than that of the alpaca (36 Mb) (Supplementary Table 15).…”
Section: Resultssupporting
confidence: 89%
“…Other cytogenetic studies on the members of this family found a diploid number of 74 in guanaco, bactrian and dromedary (Taylor et al, 1968) as well as in vicuna and bactrian (Koulischer et al, 1971); they also indicated extensive similarities in the karyotypes of these species, thus suggesting that all members of the family, including the alpaca, would have the same basic karyotype. However, discrepancies were found in the proportion of the various types of chromosomes, including the sex chromosomes.…”
mentioning
confidence: 87%
“…Los camélidos del Viejo y Nuevo Mundo presentan un cariotipo muy conservado, 2n = 74 (Taylor et al 1968;Koulischer et al 1971), con patrones de bandas G y C aparentemente muy similares (Bunch et al 1985), siendo capaces de cruzarse y producir descendencia fértil bajo influencia humana. Algunos intentos por establecer relaciones de parentesco usando métodos inmunogenéticos (Penedo et al 1988) han fallado también.…”
Section: Introductionunclassified